# How do you condense #2log a + log b – 3log c – log d#?

##### 1 Answer

Mar 24, 2016

#### Explanation:

First, bring the multiplicative constants into the logarithmic expressions using the rule:

#nlogx=log(x^n)#

Thus, we obtain:

#=log(a^2)+logb-log(c^3)-logd#

We now use the rule that combines added logarithms through multiplication of their arguments:

#logm+logn=log(mn)#

Applying this to

#log(a^2b)-log(c^3)-logd#

Opposite to adding, subtracted logarithms can have their arguments divided, in the rule:

#logm-logn=log(m/n)#

This gives the final answer of

#=log((a^2b)/(c^3d))#